Efficacy and safety of vitamin D supplementation in hospitalized COVID-19 pediatric patients: A randomized controlled trial - Zurita-Cruz, Jessie; Fonseca-Tenorio, Jeffry; Villasís-Keever, Miguel; López-Alarcón, Mardia; Parra-Ortega, Israel; López-Martínez, Briceida; Miranda-Novales, Guadalupe (Frontiers in Pediatrics, 2022)
Background Some studies suggested that adequate levels of vitamin D (VD) decrease the risk of severe COVID-19. Information about the effectiveness of VD supplementation in children is scarce. Objective To assess the efficacy and safety of VD supplementation compared to the standard of care in hospitalized children with COVID-19. Patients and methods An open-label randomized controlled single-blind clinical trial was carried out. We included patients from 1 month to 17 years, with moderate COVID-19, who required hospitalization and supplemental oxygen. They were randomized into two groups: the VD group, which received doses of 1,000 (children < 1 year) or 2,000 IU/day (from 1 to 17 years) and the group without VD (control). The outcome variables were the progression of oxygen requirement, the development of complications, and death. Statistical analysis For comparison between groups, we used the chi-squared test or Fisher's exact test and the Mann–Whitney U test. Absolute risk reduction (ARR) and the number needed to treat (NNT) were calculated. p ≤ 0.05 was considered statistically significant. Results From 24 March 2020 to 31 March 2021, 87 patients were eligible to participate in the trial; 45 patients were randomized: 20 to the VD group and 25 to the control group. There was no difference in general characteristics at baseline, including serum VD levels (median 13.8 ng/ml in the VD group and 11.4 ng/ml in the control group). Outcomes 2/20 (10%) in the VD group vs. 9/25 (36%) in the control group progressed to a superior ventilation modality (p = 0.10); one patient in the VD group died (5%) compared to 6 (24%) patients in the control group (p = 0.23). ARR was 26% (95% CI 8.8 to 60.2%) and NNT was 3 (2 to 11) for progression and ARR was 19% (95% CI −3.9 to 42.8%) and NNT was 6 (2 to 26) for death. None of the patients receiving VD had adverse effects. The trial was stopped for ethical reasons; since after receiving the results of the basal VD values, none of the patients had normal levels. Conclusion In this trial, VD supplementation in pediatric patients seems to decrease the risk of COVID-19 progression and death. More studies are needed to confirm these findings. Clinical Trial Registration This protocol was registered on ClinicalTrials.gov with the registration number NCT04502667.